G373 Management and outcomes of neonates with down syndrome admitted to neonatal units. (27th April 2016) - Morris, JK; Mann, JP; Statnikov, E; Modi, N; Johnson, N
Abstract : Aims: The aim of this study was to estimate the proportion of neonates with Down syndrome that are admitted to a neonatal unit, and compare their management and outcomes with other neonatal admissions. Methods: The number of Down syndrome live births recorded in the National Down Syndrome Cytogenetic Register was compared with the number of admissions of neonates with Down syndrome in 122 neonatal units born from 2009–2011 in the National Neonatal Research Database. For each neonate with Down syndrome identified in the NNRD, three control neonates of similar gestational age at birth (to nearest completed week), neonatal unit of admission, and month of admission were identified. Admission to a neonatal unit, length of stay, level of neonatal care, mortality and requirement for home oxygen were analysed using appropriate paired statistics. Results: 46% of neonates with Down syndrome were admitted to a neonatal unit. Boys were more likely to be admitted than girls (OR = 1.7; 95% CI: 1.4–2.0). Neonates with Down syndrome required more intensive or high dependency care compared with unaffected neonates (37% vs 27%. p < 0.01) and stayed in neonatal units for longer (11 days versus 5 days, p < 0.01). 31% of neonates with Down syndrome required respiratory support compared with 22% (p < 0.001) of unaffected neonates, and 11% were discharged requiring oxygen supplementation compared with 3% (p < 0.001) of unaffected neonates. 3% of neonates with Down syndrome died in a neonatal unit compared with 1% (p = 0.01) of unaffected neonates. Conclusion: Neonates with Down syndrome are more likely than unaffected neonates to be admitted to a neonatal unit, have a prolonged stay and be discharged home on supplemental oxygen.